Analytical and experimental study of the hexagonal metamaterial based on the distributions of the fields. Issue 3 (March 2017) - Zhang, JiaKai; Song, YiChuan; Ding, Jun; Guo, ChenJiang
ABSTRACT: In this article, a simple hexagonal metamaterial is presented. Different from the design method of parameters optimization, the method based on the analysis of the distributions of the electric field, magnetic field, and the surface current distribution is proposed. For verification of proposed analytic method, the retrieval process is carried out. Besides, the situations of the other two frequencies point are studied to further verify the analytic method. The experimental study is introduced as well. The results show that the negative effective permittivity and the negative effective permeability with pass band character is achieved simultaneously in the frequency range between 9.58 GHz to 9.75 GHz, and the comparison between the result of the analysis and the experiment justifies the proposed analytic method. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:720–726, 2017